Clinical assessment of the efficacy of low-level laser therapy on muscle pain in women with temporomandibular dysfunction, by surface electromyography - Ewerson Bertolini Shinozak; Mateus Bertolini Fernandes dos Santos; Luiz Kioaki Okazaki; Leonardo Marchini (Universidade Estadual de Campinas, 2015)
The use of low-level laser (LLL) may be an useful tool to promote reduction of muscular pain caused by TMD. Aim: This study evaluated the immediate efficacy of low-level laser therapy on women reporting pain and diagnosed with temporomandibular dysfunction (TMD). Methods: Diode laser (GaAlAs) at 790 nm wavelength (infrared spectrum) was applied as experimental treatment. Irradiations of 1.5 J/cm² were made at 4 points of the temporomandibular joint (TMJ) and of 3 J/cm² at 3 points in the temporal muscle. An electromyographic (EMG) evaluation of the masseter and anterior temporal was done at the following intervals: before, immediately after, 5 min and 20 min after laser application. Results: Comparison of the electrical activity at the times of measurement revealed a statistically significant difference in masseter muscles before (P=0.025) and immediately after (P=0.013) LLLT. Conclusions: Both masseter and temporal muscles showed a reduction in the measured EMG activities at all times after LLLT, and the temporal muscle showed higher EMG activity than the masseter muscle at all the evaluation times. LLLT caused significant immediate relaxation of the masseter muscles.